HUBUNGAN INDEKS MASSA TUBUH DAN USIA DENGAN GRADING HISTOPATOLOGI PASIEN KARSINOMA MAMMAE INVASIF NO SPECIAL TYPE DI RSPAD GATOT SOEBROTO TAHUN 2021 - Husna Bunga Jannati (2023)
Background. Malignancy in cells in the breast is called mammary carcinoma, invasive breast carcinoma no special type is the most commonly found type, in 2020 in Indonesia there were 65,858 new cases. The number of patients with invasive breast carcinoma NST at RSPAD in 2021 is 191 patients. Previous studies have shown a relationship between body mass index and age with histopathological grading of mammary carcinoma, but studies that discuss the relationship between these two variables and histopathological grading of invasive breast carcinoma NST have not been found. Objective. This study aims to determine the relationship between body mass index and age with histopathological grading of invasive breast carcinoma NST at Gatot Soebroto Army Hospital in 2021. Method. The method in this study was observational analytic and cross sectional research design, sampling using secondary data from patient medical records by simple random sampling from a population of 107 patients and a sample of 84. The frequency distribution of each variable was described in univariate analysis and the relationship between variables was analysed using bivariate analysis with chi-square test analysis. Results. There was no relationship between body mass index and histopathological grading (p=0.685), in bivariate analysis between age and histopathological grading obtained p=1 so that the relationship between the two variables was not found. The limited sample in this study and the lack of variety in the sample could be a contributing factor to the absence of an association between the two variables and the difference in results to previous studies. Conclusions. There is no association between body mass index and age variables with histopathological grading of invasive mammary carcinoma NST patients.